Social Banking - Pospíchal, Tomáš; Chalupníček, Pavel; Houdek, Petr, 1981-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2010)
My diploma thesis is about social entrepreneurship in the banking sector. The thesis has two parts - theoretical and practical. In the theoretical part I examine the social entrepreneurship in general, i.e meaning of altruism in entrepreneurship. The ambit of my interest is interesting also because for-profit and non-for-profit organizations operate or operated on the same market. The practical part contains several case studies of "social banking" institutions. Concretely, I chose charitable banks in Italy and Spain emerging in 15th century, furthermore kampeličky and Raiffeisen cooperatives, microcredit and P-to-P lending. I try to answer the question whether the "social banking" is a meaningful concept and whether we can find in history some development leading to the current form of microcredit.
Vedoucí práce: Pavel Chalupníček
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2010
Rok obhajoby 2010
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses